Node Selection Techniques in Spectrum Sharing Cooperative Cognitive Networks - Francisco Rafael Vasconcelos GuimarÃes (2013)
In this dissertation, the performance of cooperative cognitive systems with spectrum sharing is investigated. A low-complexity and high performance node selection strategy is proposed for two different of cooperative cognitive systems models. In the first model, the secondary network is composed by one source node that communicates with one among L destinations through a direct link and also assisted by one among N AF or DF relays nodes. The selected secondary destination employs a selection combining technique for choosing the best link (direct or dual-hop link) from the secondary source. Considering an underlay spectrum sharing approach, the secondary communication is performed taking into account an interference constraint, where the overall transmit power is limited by the interference at the primary receiver as well as by the maximum transmission power available at the respective nodes. An asymptotic analysis is carried out, revealing that the diversity order of the considered system is not affected by the interference, and equals to L + N. In the second model, by its turn, the secondary network is composed by one source, N AF or DF relays, and one destination. However, it is assumed the presence of M primary receivers. A relay selection strategy is proposed with the aim of maximing the end-to-end signal-to-noise ratio and, at the same time, to satisfy the interference constraints imposed by these primary receivers. After the relay selection procedure is performed, the secondary destination chooses the best path (direct link or relaying link) by employing a selection combining scheme. An asymptotic analysis is carried out, revealing that the system diversity order equals to N + 1, and showing that it is not affected neither by the number of primary receivers nor by the interference threshold. A close-form expression and an approximation for the outage probability is derived for the DF and AF protocols, respectively.